Supergrupo Minas na Serra de Bom Sucesso, extremo sudoeste do Quadrilátero Ferrífero - MG: petrografia, geoquímica e isótopos de U-Pb - Marcos Eduardo Nilton Vieira Neri (2012)
In the southwest of the Quadrilátero Ferrífero, southern portion of the Mineiro belt, is exposed the BIF-hosted Bom Sucesso Metassedimentary Sequence. This sequence comprising three units: the lower Lagoa da Prata carbonate schist, the intermediate Bom Sucesso BIF and the upper Tabuãozinho schist. U-Pb detrital zircon data from samples of the Lagoa da Prata unit indicates the maximum age of deposition of 2603 ± 7.3 Ma and correlate it with the basal Caraça Group of the Minas Supergroup. The Bom Sucesso BIF is mainly amphibolitic and it occurs interlayered with discontinuously developed ferruginous dolomite lenses grading upwards to a ferruginous metapelitic layer at the top of the unit. The geochemical signature of the banded iron formation is characterized by positive anomalies of Eu, Y and La, relative enrichment of heavy REE and absence of negative Ce anomaly, analogous to the itabirites of the Itabira Group. The mineral assemblage of the Bom Sucesso Metassedimentary Sequence indicates contact metamorphism associated with alkaline metasomatism, generated by the intrusion of Meta-granite Tabuões during Transamazonian orogeny.